2019
DOI: 10.3390/ma12172824
|View full text |Cite
|
Sign up to set email alerts
|

Performance of PATC-PDMDAAC Composite Coagulants in Low-Temperature and Low-Turbidity Water Treatment

Abstract: A novel composite was synthesized by using flocculant polyaluminum titanium silicate chloride (PATC) and poly(diallyldimethylammonium chloride) (PDMDAAC) monomers to treat low-temperature and low-turbidity water. The structure and physicochemical properties of PATC-PDMDAAC were analyzed by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis/differential scanning calorimetry (TG/DSC), X-ray diffraction spectroscopy (XRD), and scanning electron microscopy–energy dispersion spectrum (SEM-ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…15 The species reacted immediately in the initial short period is defined as Al a (usually regarded as mononuclear species); the low to medium polymeric species reacted in the following relatively longer period is defined as Al b ; the species that cannot react with ferron in limited time is defined as Al c (including high polymeric or colloidal Al species). 8 Figure 6 showed that the Al a and Al b content of the composite flocculant was significantly lower than that of PAC, while the Al c content was higher than that of PAC. It can be found that the composition of PAC and polymer leaded to the transition of polymeric Al hydrolysis species from low and medium polymeric Al species to high polymeric Al species, and increase of the molecular weight and content of polymer could deepen this transition.…”
Section: The Influences Of Polymer To Pacmentioning
confidence: 94%
See 1 more Smart Citation
“…15 The species reacted immediately in the initial short period is defined as Al a (usually regarded as mononuclear species); the low to medium polymeric species reacted in the following relatively longer period is defined as Al b ; the species that cannot react with ferron in limited time is defined as Al c (including high polymeric or colloidal Al species). 8 Figure 6 showed that the Al a and Al b content of the composite flocculant was significantly lower than that of PAC, while the Al c content was higher than that of PAC. It can be found that the composition of PAC and polymer leaded to the transition of polymeric Al hydrolysis species from low and medium polymeric Al species to high polymeric Al species, and increase of the molecular weight and content of polymer could deepen this transition.…”
Section: The Influences Of Polymer To Pacmentioning
confidence: 94%
“…[2][3][4] With the purpose of seeking more convenient, effective and cheap flocculants, and considering the poor bridging ability, large amount of sludge and the residual metal salt of inorganic flocculant, and the high cost of the organic polymer flocculants, the researchers are devoted to the inorganic-organic composite flocculants by combination the advantages of individuals. [5][6][7] Generally, there are two ways to enhance the flocculation effective of composite flocculants: One is to improve the quality and quantity of polynuclear hydroxyl metal complex ions formed by hydrolysis polymerization in inorganic flocculants, 8,9 but it is limited by the hydrolysis polymerization of the metal salt. The other is to optimize the molecular structure and molecular weight of polymer to enhance the adsorption bridging effect of composite flocculants.…”
Section: Introductionmentioning
confidence: 99%
“…When treating water at low temperature, polymer electrolytes or hybrid coagulants could be used. Zhang, Liao, and Zhu (2019) prepared a hybrid coagulant with poly aluminum titanium silicate chloride and polydienyldimethylammonium chloride (PATC-PDMDAAC). Compared with conventional coagulants, PATC-PDMDAAC had improved effect in treating water of Xiangjiang River at low temperature.…”
Section: Interfering Factorsmentioning
confidence: 99%
“…In Figure 11, the absorption peaks at 3415.24 and 1654.09 cm −1 were assigned to the stretching vibration of -NH 2 and C=O in the AM monomer, respectively [27,46]. The peak at 2932.22 cm −1 represented the asymmetric absorption peak of -CH 3 in the DMDAAC monomer, and the peak at 1449.46 cm −1 represented the stretching vibration absorption peak of -CH 2 -in the -CH 2 -N + group of DMDAAC [47]. The peak at 962.91 cm −1 represented the absorption peak of -N + (CH 3…”
Section: Infrared Spectrum Of P(am-dmdaac)mentioning
confidence: 99%